A production method for preparing ultra-light thermal insulation ceramic particles by using coal gangue
Patent Information
- Application Number
- CN202611367086.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-30
AI Technical Summary
[0006]以上现有技术所制得的陶粒,均满足国家标准要求,但主要问题:一是以上技术所制得的超轻陶粒吸水率较高,甚至接近标准限值10%,二是选用多种物料为原料,难以实现最佳配比,产品性能尤其是堆积密度、吸水率等指标稳定性不好,三是所制得的超轻陶粒未进一步处理,存在该产品与水泥胶凝物材料结合不稳固,导致的力学性能不理想和耐久性问题
(1)以煤矸石为主要原料,无需消耗黏土、页岩等天然资源,实现大宗工业固废的资源化利用,环境效益显著;
Smart Images

Figure CN123003259A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic non-metallic material preparation technology, specifically to a production method for preparing ultralight thermal insulation ceramsite using coal gangue. Background Technology
[0002] Coal gangue is a major solid waste generated during coal mining and washing. my country produces a huge amount of coal gangue annually, and its large-scale accumulation not only occupies land and pollutes the environment but also results in a serious waste of resources. Utilizing coal gangue to produce high-value-added products is currently a research hotspot in the field of comprehensive solid waste utilization.
[0003] Expanded clay aggregate (Cephalotaxus fortunei) is a type of ceramic-like particle, mostly spherical or oval in shape, with a hard outer shell that is ceramic or glazed, providing water and air insulation and giving it high strength. The particle size is generally 5–20 mm. Lightweight is the most important of Cephalotaxus fortunei's many excellent properties and the main reason it can replace heavy sand and gravel. Its internal structure consists of fine, closed-cell, honeycomb-like micropores. Cephalotaxus fortunei possesses excellent thermal insulation, fire resistance, alkali resistance, earthquake resistance, impermeability, frost resistance, and durability, and is mainly used in building materials, landscaping materials, food hygiene materials, and industrial filtration materials.
[0004] In recent years, the production and application of ordinary expanded clay aggregate in my country have increased significantly. However, this has led to problems such as generally mediocre product performance, severe homogenization within the industry, and the consumption of large quantities of natural raw materials like clay and shale, resulting in substantial waste and environmental damage. To avoid these issues, research into ultra-lightweight thermal insulation expanded clay aggregate is a crucial way to overcome these bottlenecks.
[0005] Existing technologies have made significant progress in obtaining ultralight thermal insulation ceramsite by selecting silicon carbide as a foaming agent and using quartz mica flakes, shale, fly ash, or iron tailings as raw materials, adjusting the raw material ratio, and improving process parameters. For example, patent CN112408830 B discloses a type of ceramsite and its preparation method, patent CN 112028660B discloses a composition for preparing ultralight thermal insulation ceramsite, ceramsite, and its preparation method, and the paper (Zhao Wei et al. Preparation and performance study of iron tailings-based ultralight thermal insulation ceramsite [J]. Nonmetallic Minerals, 2022, 45(2)) discloses the preparation and performance study of iron tailings-based ultralight thermal insulation ceramsite.
[0006] The ceramsite produced by the above-mentioned existing technologies all meet the requirements of national standards, but the main problems are: First, the water absorption rate of the ultra-light ceramsite produced by the above technologies is relatively high, even close to the standard limit of 10%; second, it is difficult to achieve the best ratio by using a variety of materials as raw materials, and the product performance, especially the stability of indicators such as bulk density and water absorption rate, is not good; third, the ultra-light ceramsite produced is not further processed, and there is an unstable bond between the product and cementitious materials, resulting in unsatisfactory mechanical properties and durability problems. Summary of the Invention
[0007] Based on this, the purpose of this invention is to provide a production method for preparing ultralight thermal insulation ceramsite using coal gangue, so as to obtain high-performance ultralight thermal insulation ceramsite products.
[0008] The objective of this invention is achieved through the following technical solution: A method for producing ultralight thermal insulation ceramsite using coal gangue includes the following steps: (1) Raw material preparation The coal gangue is crushed, graded, and sorted to obtain coal gangue raw materials with high silicon and aluminum content. (2) Raw material ratio SiO2, silicon nitride powder and NaOH granules are added to the coal gangue raw material, and the mixture is thoroughly mixed, pelletized and dried to obtain a mixture. (3) Expansion due to heating The mixture is heated and expanded, then naturally cooled to room temperature to obtain the initial product of ultra-lightweight thermal insulation ceramsite. (4) Spraying and baking The initial ultralight thermal insulation ceramsite product is evenly covered with an adhesive, and then heated and baked to obtain the ultralight thermal insulation ceramsite product.
[0009] Preferably, the high silicon and aluminum content coal gangue raw material in step (1) has a particle size of 200-250 mesh, a silicon content of more than 60% as SiO2, an aluminum content of more than 15% as Al2O3, and a carbon content of 1-3% as C.
[0010] Preferably, the mixture in step (2) has the following composition: silicon content of more than 70% based on SiO2, aluminum content of more than 15% based on Al2O3, carbon content of 1~3% based on C, silicon nitride content of 0.5~1% based on Si3N4, and NaOH content of 1~5%.
[0011] Preferably, the particle size of the pelletized mixture in step (2) is 5 to 20 mm.
[0012] Preferably, the drying temperature in step (2) is ≥105℃ and the time is ≥2h.
[0013] Preferably, the heating and expansion in step (3) adopts a stepped heating and heat preservation treatment: first, the temperature is raised to 600-620℃ at a rate of 5-8℃ / min and held for 15-30 min; then the temperature is raised to 800-900℃ at a rate of 5-8℃ / min and held for 15-20 min; then the temperature is raised to 1330-1500℃ at a rate of 5-8℃ / min and held for 10-20 min.
[0014] Preferably, the adhesive in step (4) is polyacrylic acid; the amount of the adhesive is 1 / 3 to 2 / 3 of the initial mass of the ultralight thermal insulation ceramic particles.
[0015] Preferably, the adhesive in step (4) is added by spraying. The adhesive is sprayed from top to bottom 2 to 3 times, and after turning the ceramsite over, it is sprayed 1 to 2 more times until the surface of the ceramsite is completely and evenly covered.
[0016] Preferably, the heating and baking process in step (4) involves first heating to 180-200℃ at a rate of 3-5℃ / min and baking for 30-40 minutes; then heating to 250-280℃ at a rate of 3-5℃ / min and baking for 20-25 minutes.
[0017] This invention uses all coal gangue as raw material, with appropriate additions of SiO2 and foaming agents NaOH and Si3N4. By adjusting the raw material ratio and optimizing process parameters, a three-stage heating and expansion process is employed. The first stage, holding at 600℃ in the low-temperature range, utilizes the inherent expansion characteristics of the coal gangue to generate gas. The temperature is then increased to 800℃~830℃ and held, representing the second stage of gas generation, utilizing the reaction between NaOH and SiO2. Finally, the temperature is increased to 1330℃~1350℃ and held, representing the tertiary stage of gas generation, utilizing the oxidative decomposition of Si3N4 to produce gas. This process yields stable ultralight ceramsite with a bulk density of 172~249 kg / m³. 3 The compressive strength of the ceramsite is above 5.0 MPa. At the same time, the obtained ceramsite is sprayed with a binder to obtain ultra-lightweight ceramsite with better performance, which is suitable for thermal insulation concrete application in the maintenance structure of high-rise buildings.
[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) Using coal gangue as the main raw material, without consuming natural resources such as clay and shale, it realizes the resource utilization of bulk industrial solid waste, resulting in significant environmental benefits; (2) Using a composite foaming agent of NaOH and Si3N4, combined with a three-stage segmented heating and expansion process, the gas is generated by the expansion characteristics of coal gangue itself in the low-temperature stage, by the reaction of NaOH and SiO2 in the medium-temperature stage, and by the oxidation and decomposition of Si3N4 in the high-temperature stage. The three stages of gas generation are connected in an orderly manner, and the resulting ceramsite has a bulk density as low as 172~249 kg / m³. 3 The compressive strength of the cylinder reaches 5.0 MPa or above, the water absorption rate is low in 1 hour, the performance is stable, and the batch consistency is good; all performance indicators meet the requirements of GB / T 17431.1-2010 "Lightweight aggregates and their test methods - Part 1: Lightweight aggregates".
[0019] (3) By spraying an adhesive onto the surface of the ceramsite and baking it, the bonding strength between the ceramsite and the cementitious material is enhanced, the mechanical properties and durability of the lightweight aggregate concrete are improved, and the added value of the product is increased. (4) The high-performance ultra-light thermal insulation ceramic pellets obtained by the present invention not only have the advantages of being ultra-light, high-performance, and high-value, but also can dispose of coal gangue waste, turning waste into treasure, and have wide applicability, extremely high application value and environmental benefits. Attached Figure Description
[0020] Figure 1 This is a flowchart of the production method for preparing ultralight thermal insulation ceramsite using coal gangue according to the present invention. Detailed Implementation
[0021] The chemical composition of the coal gangue used in this invention, calculated as oxides, is as follows: SiO2 52-65; Al2O3 16-36; Fe2O3 2.28-14.63; CaO 0.1-2.3; MgO 0.1-2.5; K2O+Na2O 0.1-3.1.
[0022] The production method for preparing ultralight thermal insulation ceramsite using coal gangue according to the present invention includes the following steps: (1) Raw material preparation The coal gangue is crushed, graded and sorted to obtain coal gangue raw materials with high silicon and aluminum content, consisting of 200-250 mesh particles, carbon content (calculated as C) of 1-3%, silicon content (calculated as SiO2) of more than 60%, and aluminum content (calculated as Al2O3) of more than 15%. (2) Raw material ratio Add SiO2, silicon nitride powder and NaOH granular alkali to the coal gangue raw material, mix thoroughly, pelletize, and dry (temperature ≥105℃, ≥2h) to obtain a mixture with a silicon content (calculated as SiO2) of more than 70%, an aluminum content (calculated as Al2O3) of more than 15%, a carbon content (calculated as C) of 1~3%, a silicon nitride content (calculated as Si3N4) of 0.5~1%, a NaOH (granular alkali) content of 1~5%, and a particle size of 5~20mm. (3) Expansion due to heating The mixture is heated and expanded. First, the temperature is increased to 600-620℃ at a rate of 5-8℃ / min and held for 15-30 min. Then, the temperature is increased to 800-900℃ at a rate of 5-8℃ / min and held for 15-20 min. Next, the temperature is increased to 1330-1500℃ at a rate of 5-8℃ / min and held for 10-20 min. Finally, it is naturally cooled to room temperature to obtain the initial product of ultra-lightweight thermal insulation ceramsite. (4) Spraying and baking The initial ultralight thermal insulation ceramsite is sprayed with a binder of 1 / 3 to 2 / 3 by mass from top to bottom 2 to 3 times. After turning the ceramsite over, it is sprayed 1 to 2 more times until the surface of the ceramsite is completely and evenly covered. Then, it is heated and baked. First, the temperature is increased to 180-200℃ at a rate of 3-5℃ / min and baked for 30 to 40 minutes. Then, the temperature is increased to 250-280℃ at a rate of 3-5℃ / min and baked for 20 to 25 minutes to obtain the ultralight thermal insulation ceramsite product.
[0023] In specific embodiments of the present invention, unless otherwise specified, the proportions of the raw materials are all mass ratios.
[0024] Example 1 A production method for preparing ultralight thermal insulation ceramsite using coal gangue, comprising the following steps: (1) Raw material preparation The coal gangue is crushed, graded and sorted to obtain coal gangue raw materials with high silicon and aluminum content, consisting of 200-250 mesh particles, carbon content (calculated as C) of 2.1%, silicon content (calculated as SiO2) of 63%, and aluminum content (calculated as Al2O3) of 15.7%. (2) Raw material ratio SiO2, silicon nitride powder, and NaOH granules were added to the coal gangue raw material, and the mixture was thoroughly mixed, pelletized, and dried (at 105℃ for 2 hours) to obtain a mixture with SiO2 content of 71.1%, Al2O3 content of 15.3%, Fe2O3 content of 5.5%, C content of 1.5%, MgO content of 2.2%, CaO content of 1.0%, K2O+Na2O content of 1.7%, Si3N4 content of 0.5%, NaOH content of 1.2%, and a particle size of 5-20 mm. (3) Expansion due to heating The mixture was placed in a muffle furnace and heated to 600°C at a rate of 5°C / min and held for 20 min; then heated to 800°C at a rate of 5°C / min and held for 15 min; then heated to 1330°C at a rate of 5°C / min and held for 10 min; and then cooled naturally to room temperature to obtain the initial product of ultralight thermal insulation ceramsite. (4) Spraying and baking The initial ultralight thermal insulation ceramic aggregate was sprayed three times from top to bottom with a binder of 1 / 3 by mass of polyacrylic acid. After turning the ceramic aggregate over, it was sprayed twice more to completely and evenly cover the surface of the ceramic aggregate. Then, the temperature was increased to 200°C at a rate of 5°C / min and baked for 30 minutes. Then, the temperature was increased to 250°C at a rate of 5°C / min and baked for 20 minutes to obtain the ultralight thermal insulation ceramic aggregate product.
[0025] The resulting ultralight thermal insulation ceramsite has a compressive strength of 5.2 MPa and a bulk density of 242 kg / m³. 3 The water absorption rate in 1 hour was 3.2%, the mud content was 1.1%, the mud lump content was 0.4%, the boiling mass loss was 3.1%, and the loss on ignition was 2.9%.
[0026] Example 2 A production method for preparing ultralight thermal insulation ceramsite using coal gangue, comprising the following steps: (1) Raw material preparation The coal gangue is crushed, graded and sorted to obtain coal gangue raw materials with high silicon and aluminum content, consisting of 200-250 mesh particles, carbon content (calculated as C) of 1.9%, silicon content (calculated as SiO2) of 67.2%, and aluminum content (calculated as Al2O3) of 17.1%. (2) Raw material ratio SiO2, silicon nitride powder, and NaOH granules were added to the coal gangue raw material, and the mixture was thoroughly mixed, pelletized, and dried (at 105℃ for 2 hours) to obtain a mixture with SiO2 content of 73.1%, Al2O3 content of 16.2%, Fe2O3 content of 2.9%, C content of 1.6%, MgO content of 2.5%, CaO content of 0.9%, K2O+Na2O content of 0.8%, Si3N4 content of 0.6%, NaOH content of 1.4%, and a particle size of 5-20 mm. (3) Expansion due to heating The mixture was placed in a muffle furnace and heated to 600°C at a rate of 5°C / min and held for 25 min; then heated to 800°C at a rate of 5°C / min and held for 18 min; then heated to 1340°C at a rate of 5°C / min and held for 12 min; and then cooled naturally to room temperature to obtain the initial product of ultra-light thermal insulation ceramsite. (4) Spraying and baking The initial ultralight thermal insulation ceramic aggregate was sprayed three times from top to bottom with a binder of 1 / 3 by mass of polyacrylic acid. After turning the ceramic aggregate over, it was sprayed twice more to completely and evenly cover the surface of the ceramic aggregate. Then, the temperature was increased to 200°C at a rate of 5°C / min and baked for 30 minutes. Then, the temperature was increased to 250°C at a rate of 5°C / min and baked for 20 minutes to obtain the ultralight thermal insulation ceramic aggregate product.
[0027] The resulting ultralight thermal insulation ceramsite has a compressive strength of 5.5 MPa and a bulk density of 249 kg / m³. 3 The water absorption rate in 1 hour is 3.5%, the mud content is 1.5%, the mud lump content is 0.7%, the boiling mass loss is 3.5%, and the loss on ignition is 3.4%.
[0028] Example 3 A production method for preparing ultralight thermal insulation ceramsite using coal gangue, comprising the following steps: (1) Raw material preparation The coal gangue is crushed, graded and sorted to obtain high-silicon-aluminum coal gangue raw materials with 200-250 mesh particles, carbon content (C) of 2.1%, silicon content (SiO2) of 68.3% and aluminum content of 15.5%. (2) Raw material ratio SiO2, silicon nitride powder, and NaOH granules were added to the coal gangue raw material, and the mixture was thoroughly mixed, pelletized, and dried (at 105℃ for 2 hours) to obtain a mixture with SiO2 content of 74.0%, Al2O3 content of 15.2%, Fe2O3 content of 3.3%, C content of 1.9%, MgO content of 0.3%, CaO content of 1.1%, K2O+Na2O content of 1.2%, Si3N4 content of 0.9%, NaOH content of 2.1%, and a particle size of 5-20 mm. (3) Expansion due to heating The mixture was placed in a muffle furnace and heated to 600°C at a rate of 6°C / min, and held for 25 min; then heated to 800°C at a rate of 6°C / min, and held for 20 min; then heated to 1340°C at a rate of 6°C / min, and held for 14 min; and then cooled naturally to room temperature to obtain the initial product of ultralight thermal insulation ceramsite. (4) Spraying and baking The initial ultra-light thermal insulation ceramic aggregate was sprayed three times from top to bottom with a binder of 1 / 3 by mass of polyacrylic acid. After turning the ceramic aggregate over, it was sprayed twice more to completely and evenly cover the surface of the ceramic aggregate. Then, the temperature was increased to 200°C at a rate of 3°C / min and baked for 30 minutes. Then, the temperature was increased to 250°C at a rate of 3°C / min and baked for 20 minutes to obtain the ultra-light thermal insulation ceramic aggregate product.
[0029] The resulting ultralight thermal insulation ceramsite has a compressive strength of 5.1 MPa and a bulk density of 189 kg / m³. 3 The water absorption rate in 1 hour was 3.9%, the mud content was 1.0%, the mud lump content was 0.3%, the boiling mass loss was 2.5%, and the loss on ignition was 3.8%.
[0030] Example 4 A production method for preparing ultralight thermal insulation ceramsite using coal gangue, comprising the following steps: (1) Raw material preparation The coal gangue is crushed, graded and sorted to obtain coal gangue raw materials with high silicon and aluminum content, consisting of 200-250 mesh particles, carbon content (calculated as C) of 2.3%, silicon content (calculated as SiO2) of 67.4%, and aluminum content (calculated as Al2O3) of 16.2%. (2) Raw material ratio SiO2, silicon nitride powder, and NaOH granules were added to the coal gangue raw material, and the mixture was thoroughly mixed, pelletized, and dried (at 105℃ for 2 hours) to obtain a mixture with SiO2 content of 73.2%, Al2O3 content of 15.8%, Fe2O3 content of 4.2%, C content of 2.0%, MgO content of 0.4%, CaO content of 0.5%, K2O+Na2O content of 0.5%, Si3N4 content of 1.0%, NaOH content of 2.4%, and a particle size of 5-20 mm. (3) Expansion due to heating The mixture was placed in a muffle furnace and heated to 600°C at a rate of 6°C / min, and held for 27 min; then heated to 800°C at a rate of 6°C / min, and held for 20 min; then heated to 1340°C at a rate of 6°C / min, and held for 15 min; and then naturally cooled to room temperature to obtain the initial product of ultralight thermal insulation ceramsite. (4) Spraying and baking The initial ultra-light thermal insulation ceramic aggregate was sprayed three times from top to bottom with a binder of 1 / 3 by mass of polyacrylic acid. After turning the ceramic aggregate over, it was sprayed twice more to completely and evenly cover the surface of the ceramic aggregate. Then, the temperature was increased to 200°C at a rate of 4°C / min and baked for 35 minutes. Then, the temperature was increased to 250°C at a rate of 4°C / min and baked for 25 minutes to obtain the ultra-light thermal insulation ceramic aggregate product.
[0031] The resulting ultralight thermal insulation ceramsite has a compressive strength of 5.0 MPa and a bulk density of 177 kg / m³. 3 The water absorption rate in 1 hour was 4.2%, the mud content was 0.8%, the mud lump content was 0.5%, the boiling mass loss was 2.0%, and the loss on ignition was 3.2%.
[0032] Example 5 A production method for preparing ultralight thermal insulation ceramsite using coal gangue, comprising the following steps: (1) Raw material preparation The coal gangue is crushed, graded and sorted to obtain coal gangue raw materials with high silicon and aluminum content, consisting of 200-250 mesh particles, carbon content (calculated as C) of 1.2%, silicon content (calculated as SiO2) of 66.8% and aluminum content (calculated as Al2O3) of 15.6%. (2) Raw material ratio SiO2, silicon nitride powder, and NaOH granular alkali were added to the coal gangue raw material, and the mixture was thoroughly mixed, pelletized, and dried (at 105℃ for 2 hours) to obtain a mixture with SiO2 content of 75.0%, Al2O3 content of 15.1%, Fe2O3 content of 2.1%, C content of 1.0%, MgO content of 0.8%, CaO content of 1.5%, K2O+Na2O content of 1.1%, Si3N4 content of 0.9%, NaOH content of 2.5%, and a particle size of 5-20 mm. (3) Expansion due to heating The mixture was placed in a muffle furnace and heated to 600°C at a rate of 7°C / min and held for 29 min; then heated to 800°C at a rate of 7°C / min and held for 20 min; then heated to 1340°C at a rate of 7°C / min and held for 17 min; and then cooled naturally to room temperature to obtain the initial product of ultralight thermal insulation ceramsite. (4) Spraying and baking The initial ultralight thermal insulation ceramic aggregate was sprayed three times from top to bottom with a binder of 1 / 3 by mass of polyacrylic acid. After turning the ceramic aggregate over, it was sprayed twice more to completely and evenly cover the surface of the ceramic aggregate. Then, the temperature was increased to 200°C at a rate of 3°C / min and baked for 35 minutes. Then, the temperature was increased to 250°C at a rate of 3°C / min and baked for 25 minutes to obtain the ultralight thermal insulation ceramic aggregate product.
[0033] The resulting ultralight thermal insulation ceramsite has a compressive strength of 5.1 MPa and a bulk density of 176 kg / m³. 3 The water absorption rate in 1 hour was 4.7%, the mud content was 1.1%, the mud lump content was 0.9%, the boiling mass loss was 2.4%, and the loss on ignition was 2.3%.
[0034] Example 6 A production method for preparing ultralight thermal insulation ceramsite using coal gangue, comprising the following steps: (1) Raw material preparation The coal gangue is crushed, graded and sorted to obtain coal gangue raw materials with high silicon and aluminum content, consisting of 200-250 mesh particles, carbon content (calculated as C) of 1.4%, silicon content (calculated as SiO2) of 69.2% and aluminum content (calculated as Al2O3) of 15.9%. (2) Raw material ratio SiO2, silicon nitride powder, and NaOH granules were added to the coal gangue raw material, and the mixture was thoroughly mixed, pelletized, and dried (at 105℃ for 2 hours) to obtain a mixture with SiO2 content of 74.9%, Al2O3 content of 15.5%, Fe2O3 content of 2.0%, C content of 1.1%, MgO content of 0.6%, CaO content of 0.9%, K2O+Na2O content of 1.0%, Si3N4 content of 1.0%, NaOH content of 3.0%, and a particle size of 5-20 mm. (3) Expansion due to heating The mixture was placed in a muffle furnace and heated to 600°C at a rate of 7°C / min and held for 30 min; then heated to 800°C at a rate of 7°C / min and held for 20 min; then heated to 1350°C at a rate of 7°C / min and held for 20 min; and then cooled naturally to room temperature to obtain the initial product of ultra-light thermal insulation ceramsite. (4) Spraying and baking The initial ultra-light thermal insulation ceramic aggregate was sprayed three times from top to bottom with a binder of 1 / 3 by mass of polyacrylic acid. After turning the ceramic aggregate over, it was sprayed twice more to completely and evenly cover the surface of the ceramic aggregate. Then, the temperature was increased to 200°C at a rate of 4°C / min and baked for 35 minutes. Then, the temperature was increased to 250°C at a rate of 4°C / min and baked for 25 minutes to obtain the ultra-light thermal insulation ceramic aggregate product.
[0035] The resulting ultralight thermal insulation ceramsite has a compressive strength of 5.0 MPa and a bulk density of 172 kg / m³. 3 The water absorption rate in 1 hour was 4.9%, the mud content was 1.4%, the mud lump content was 1.0%, the boiling mass loss was 3.5%, and the loss on ignition was 4.0%.
[0036] Comparative Example 1 A production method for preparing ultralight thermal insulation ceramic particles using coal gangue, the raw material composition and preparation method are the same as in Example 1, except that SiO2 is not added in step (2) of Comparative Example 1.
[0037] The resulting ultralight thermal insulation ceramsite has a compressive strength of 1.7 MPa and a bulk density of 120 kg / m³. 3 The water absorption rate in 1 hour was 15.2%, the mud content was 5.6%, the mud lump content was 4.2%, the boiling mass loss was 6.1%, and the loss on ignition was 12%.
[0038] Comparative Example 2 A production method for preparing ultralight thermal insulation ceramic particles using coal gangue, the raw material composition and preparation method are the same as in Example 1, except that silicon nitride powder is not added in step (2) of Comparative Example 2.
[0039] The resulting ultralight thermal insulation ceramsite has a compressive strength of 3.1 MPa and a bulk density of 310 kg / m³. 3 The water absorption rate in 1 hour was 5.8%, the mud content was 1.8%, the mud lump content was 1.2%, the boiling mass loss was 3.9%, and the loss on ignition was 4.5%.
[0040] Comparative Example 3 A production method for preparing ultralight thermal insulation ceramic granules using coal gangue, the raw material composition and preparation method are the same as in Example 1, except that in step (2) of Comparative Example 3, no NaOH granular alkali is added.
[0041] The resulting ultralight thermal insulation ceramsite has a compressive strength of 2.5 MPa and a bulk density of 320 kg / m³. 3 The water absorption rate in 1 hour was 8.5%, the mud content was 2.2%, the mud lump content was 1.7%, the boiling mass loss was 5.9%, and the loss on ignition was 5.8%.
[0042] Comparative Example 4 A production method for preparing ultralight thermal insulation ceramsite using coal gangue, the raw material composition and preparation method are the same as in Example 1, except that in Comparative Example 4, step (3) the mixture is placed in a muffle furnace, heated to 1330°C at a rate of 5°C / min, and kept at that temperature for 45 min; then naturally cooled to room temperature to obtain the initial product of ultralight thermal insulation ceramsite.
[0043] The resulting ultralight thermal insulation ceramsite has a compressive strength of 3.1 MPa and a bulk density of 350 kg / m³. 3 The water absorption rate in 1 hour was 5.1%, the mud content was 1.6%, the mud lump content was 1.4%, the boiling mass loss was 3.4%, and the loss on ignition was 4.1%.
[0044] Comparative Example 5 A production method for preparing ultralight thermal insulation ceramic granules using coal gangue. The raw material composition and preparation method are the same as in Example 1. The difference is that in Comparative Example 5, step (4) spraying and baking is carried out by heating to 250°C at a rate of 8°C / min and baking for 50min to obtain ultralight thermal insulation ceramic granule products.
[0045] The resulting ultralight thermal insulation ceramsite has a compressive strength of 3.6 MPa and a bulk density of 332 kg / m³. 3 The water absorption rate in 1 hour was 7.9%, the mud content was 2.3%, the mud lump content was 1.8%, the boiling mass loss was 3.5%, and the loss on ignition was 5.2%.
[0046] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for producing ultralight thermal insulation ceramsite using coal gangue, characterized in that, Includes the following steps: (1) Raw material preparation The coal gangue is crushed, graded, and sorted to obtain coal gangue raw materials with high silicon and aluminum content. (2) Raw material ratio SiO2, silicon nitride powder and NaOH granules are added to the coal gangue raw material, and the mixture is thoroughly mixed, pelletized and dried to obtain a mixture. (3) Expansion due to heating The mixture is heated and expanded, then naturally cooled to room temperature to obtain the initial product of ultra-lightweight thermal insulation ceramsite. (4) Spraying and baking The initial ultralight thermal insulation ceramsite is evenly covered with an adhesive, and then heated and baked to obtain the ultralight thermal insulation ceramsite product.
2. The production method for preparing ultralight thermal insulation ceramsite using coal gangue according to claim 1, characterized in that, The high-silicon-aluminum coal gangue raw material in step (1) has a particle size of 200-250 mesh, a silicon content of more than 60% as SiO2, an aluminum content of more than 15% as Al2O3, and a carbon content of 1-3% as C.
3. The production method for preparing ultralight thermal insulation ceramsite using coal gangue according to claim 1, characterized in that, The mixture in step (2) has the following composition: silicon content of more than 70% based on SiO2, aluminum content of more than 15% based on Al2O3, carbon content of 1~3% based on C, silicon nitride content of 0.5~1% based on Si3N4, and NaOH content of 1~5%.
4. The production method for preparing ultralight thermal insulation ceramsite using coal gangue according to claim 1, characterized in that, The particle size of the pelletized mixture in step (2) is 5-20 mm.
5. The production method for preparing ultralight thermal insulation ceramsite using coal gangue according to claim 1, characterized in that, The drying temperature in step (2) is ≥105℃ and the time is ≥2h.
6. The production method for preparing ultralight thermal insulation ceramsite using coal gangue according to claim 1, characterized in that, The heating and expansion process described in step (3) is carried out using a stepped heating and holding treatment. First, the temperature is increased to 600-620℃ at a rate of 5-8℃ / min and held for 15-30 min. Then, the temperature is increased to 800-900℃ at a rate of 5-8℃ / min and held for 15-20 min. Finally, the temperature is increased to 1330-1500℃ at a rate of 5-8℃ / min and held for 10-20 min.
7. The production method for preparing ultralight thermal insulation ceramsite from coal gangue according to claim 1, characterized in that, The adhesive used in step (4) is polyacrylic acid; the amount of adhesive used is 1 / 3 to 2 / 3 of the initial mass of the ultra-light thermal insulation ceramic granules.
8. The production method for preparing ultralight thermal insulation ceramsite using coal gangue according to claim 1, characterized in that, In step (4), the adhesive is added by spraying. The adhesive is sprayed from top to bottom 2 to 3 times. After turning the ceramsite over, it is sprayed 1 to 2 more times until the surface of the ceramsite is completely and evenly covered.
9. The production method for preparing ultralight thermal insulation ceramsite using coal gangue according to claim 1, characterized in that, Step (4) involves a stepped heating and heat preservation process. First, the temperature is increased to 180-200℃ at a rate of 3-5℃ / min, and then baked for 30-40 minutes. Next, the temperature is increased to 250-280℃ at a rate of 3-5℃ / min, and then baked for 20-25 minutes.
Citation Information
Patent Citations
Composition for preparing ultralight ceramsite, ceramsite and preparation method thereof
CN112028660B
A type of ceramsite and its preparation method
CN112408830B